Resource utilization by deep-sea sharks at the Le Danois Bank, Cantabrian Sea, north-east Atlantic Ocean - Preciado, Izaskun; Cartes, Joan Enric; Serrano, Alberto; Velasco, Francisco; Olaso, Ignacio; Sánchez, Francisco; Frutos, I. (Journal of Fish Biology, 2009)
25 pages, 8 figures, 3 tables The feeding habits of birdbeak dogfish Deania calcea, velvet belly lantern shark Etmopterus spinax and blackmouth catshark Galeus melastomus at Le Danois Bank, Cantabrian Sea, south Bay of Biscay were studied in relation to their bathymetric distribution. Deep-sea sharks were collected during two multidisciplinary surveys carried out in October 2003 and April 2004 at the Le Danois Bank. Two different habitats were defined: (1) the top of the bank, ranging from 454 to 642 m depth and covered by fine-sand sediments with a low percentage of organic matter, and (2) the inner basin located between the bank and the Cantabrian Sea’s continental shelf, at depths of 810–1048 m, which was characterized by a high proportion of silt and organic matter. Deania calcea was not present at the top of the bank but was abundant below 642 m, while E. spinax was abundant in the shallower top of the bank but was not found in the deeper inner basin. There was almost no bathymetric overlap between these two deep-sea shark species. Galeus melastomus was found over the whole depth range. There seemed to be an ontogenetic segregation with depth for this species, however, since 80% of the specimens collected at the top of the bank were <600 mm total length (LT) (mean 510 mm LT), whereas larger individuals (mean 620 mm LT) inhabited deeper zones. Galeus melastomus exhibited a significantly higher feeding intensity than both E. spinax at the top of the bank and D. calcea in the inner basin. Little dietary overlap between D. calcea and G. melastomus in the inner basin was found, with D. calcea being an ichthyophagous predator while the diet of G. melastomus at these depths was composed of a variety of meso-bathypelagic shrimps (e.g. Acantephyra pelagica, Pasiphaea spp. and Sergia robusta), cephalopods and fishes. The diets of E. spinax and G. melastomus at the top of the bank showed a high dietary overlap of euphausiids, which represented the main prey taxa for both species. Euphausiids declined in abundance ...